Development of IPAS Teaching Materials Based on Javanese Local Wisdom in Differentiated Learning for Students - Isrotun, Umi; Muhtarom, Muhtarom; Buchori, Achmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to develop teaching materials based on Javanese local wisdom in differentiated learning to improve students’ creativity in the IPAS subject at the elementary school level. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The population in this study was all fourth-grade students at the elementary school where the research was conducted. The sampling technique used was purposive sampling, which involves selecting a sample based on specific considerations relevant to the research objectives. The sample consisted of 21 fourth-grade students. Furthermore, the study involved expert validators consisting of learning material experts, learning media experts, and learning design experts to assess the feasibility of the developed teaching materials. The data in this study were obtained from expert validators and fourth-grade elementary school students through validation sheets, questionnaires, observations, and tests. The data analysis techniques included descriptive quantitative analysis to determine the validity and practicality of the teaching materials, as well as inferential statistical analysis using N-gain and paired sample t-test to evaluate their effectiveness. The results showed that the teaching materials were very valid, with an average validation score of 4.55. They were also considered very practical, indicated by student response scores of 4.08 and teacher response scores of 4.63. In terms of effectiveness, there was an increase in the average pretest score (2.63) to posttest (4.25), with an N-Gain of 0.68 (moderate category) and a significant difference (Sig. 0.000 < 0.05). Therefore, the developed teaching materials are valid, practical, and effective in enhancing students’ creativity and can be used as an alternative learning resource in elementary education.